The impact of social trust on attitude towards the welfare state: the case of Turkey - Coşar, Tamer. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2015., 2015)
The significance of the concept of social trust has increased in recent years, particularly within the context of the welfare state. This thesis examines social trust (conceptualized as generalized inter-personal trust) in order to evaluate whether it has an impact on attitudes towards the welfare state in Turkey when social-demographic factors (such as gender, age, years of education, discrimination and ethnic group affiliation, unemployment, type of organization worked for, household income, language at home, and the placement of individuals along the left-right ideological spectrum and subjective well-being index -life satisfaction and happiness) are controlled for. This thesis uses quantitative methods and the 4th round of European Social Survey data of 2008 in order to evaluate whether the specific case of Turkey entails a correlation between the level of trust and the attitudes towards the welfare state. The result illustrates that there is a u-shaped relationship between social trust and welfare state in Turkey: individuals who claim they do not trust others and those who claim they trust others tend to have more positive attitude towards government responsibilities whereas those who are situated in the middle have a negative attitudes towards welfare state responsibilities.
Keywords: Trust -- Social aspects.; Welfare state -- Turkey.